Synthesis, physical and mechanical properties of lead strontium titanate glass ceramics - Shweta; Gautam C.; Tripathi V.P.; Kumar S.; Behera S.; Gautam R.K. (My University, 2025)
Various glass composition, x = 0.0, 0.2, 0.4 and 0.6 were synthesized in a bulky glass system 64 [(Pb1-xSrx)OTiO2]-25 [(2SiO2·B2O3)]-[3BaO·7K2O]-1La2O3 using melt-quenching technique. All synthesized glasses were converted into their glass ceramics via a scalable solid-state reaction method. Several physical parameters were investigated such as green/sintered density, oxygen packing density, ionic concentrations, molar volume, and molar mass respectively. For phase identification of the sintered glass ceramics, X-Ray diffraction measurements were performed. Further, to evaluate structural properties of the sintered glass ceramic samples, FTIR spectroscopy was also performed. To reveal the grain/grain boundaries and elemental analysis, surface morphology of the sintered glass ceramics followed by energy dispersive X-ray analysis was evaluated by employing a scanning electron microscopic technique. Further, to study the mechanical properties of these glass ceramics, tribological tests were also conducted, and revealed the maximum value of compressive strength, 322 MPa for glass ceramic, x = 0.6 sintered at 796 °C. © 2021 Elsevier B.V.